Possibilities of the Functional Analysis of Verbal Behavior for the Clinical Practice - Queiroz, Luciano Barbosa de; Medeiros, Fabio Hernandez de (Perspectivas em Análise do Comportamento, 2022)
Most of the data available to the therapist’s assessment and intervention is the client's verbal behavior. Nevertheless, there is little literature that addresses the possible contributions of the analysis of verbal operants to therapy. Although it is possible to find in the analytical-behavioral literature other theoretical paradigms about phenomena traditionally studied as "language", Skinner's proposal for functional analysis of verbal behavior deserves further development and proves to be potentially fruitful. The aim of this article is to investigate and discuss how the analysis of verbal behavior may support the evaluation and therapeutic intervention. The theoretical-conceptual exposition of this work indicates that clinical practice can be improved if the therapist makes such functional analyzes. It is concluded that there is a need for conducting empirical research on the topic and for the pragmatic evaluation of the considerations presented in this article.